Ta2O5 coatings modified with CdS, ZnO, and Dy2O3 particles prepared by plasma electrolytic oxidation of tantalum for the photocatalytic degradation of methyl orange - Stojadinović, Stevan; Perković, Mladen; Radić, Nenad (Solid state sciences, 2024)
Ta2O5/CdS, Ta2O5/ZnO and Ta2O5/Dy2O3 coatings for application in photocatalytic degradation of methyl orange were prepared by plasma electrolytic oxidation of tantalum in an alkaline electrolyte with different concentrations of CdS, ZnO, and Dy2O3 particles up to 2.0 g/L. The coatings were characterized by SEM/EDS, XRD, Raman spectroscopy, DRS and photoluminescence spectroscopy. The morphology, thickness, phase structure and absorption properties of all coatings are almost identical and independent of the content of CdS, ZnO, and Dy2O3 embedded in Ta2O5 coatings. The orthorhombic and monoclinic phases of Ta2O5 are the main constituents of the coatings. Due to the low content of embedded CdS, ZnO, and Dy2O3 in Ta2O5 coatings, they exhibit high absorption in the middle ultraviolet region, which is characteristic of Ta2O5. The photocatalytic activity (PA) of Ta2O5/CdS, Ta2O5/ZnO and Ta2O5/Dy2O3 is higher than that of pure Ta2O5 and depends on the amount of CdS, ZnO, and Dy2O3 in the electrolyte, respectively. The highest PA was observed for coatings formed in an electrolyte containing 0.5 g/L of CdS, ZnO, and Dy2O3. The improved PA of Ta2O5/CdS, Ta2O5/ZnO and Ta2O5/Dy2O3 compared to Ta2O5 is related to the reduction of photogenerated electron/hole recombination. The mechanism of the photogenerated electron/hole transfer process is presented and discussed. [Display omitted] •PEO coatings are formed on Ta in alkaline electrolyte containing CdS, ZnO, and Dy2O3.•Ta2O5/CdS, Ta2O5/ZnO and Ta2O5/Dy2O3 primarily consist of the orthorhombic phase of Ta2O5.•Compared to Ta2O5, the PA of Ta2O5/CdS, Ta2O5/ZnO, and Ta2O5/Dy2O3 is higher.•Concentration of CdS, ZnO, and Dy2O3 particles significantly impacts PA.•The highest PA coatings are formed in electrolytes containing 0.5 g/L of CdS, ZnO, and Dy2O3.